LORENTZ NUMBER WITH PHENOMENOLOGICAL TRANSMISSION - GROSU, I. (Studia Universitatis Babeș-Bolyai Physica, 2021)
We analyzed the Lorentz number for thermoelectric phenomena in the case of electronic systems, using the Landauer-Bϋttiker method. For the transmission coefficient we will adopt two simple phenomenological forms, constant and linear. The case of graphene with a quadratic transmission is also analyzed.